2012
DOI: 10.5588/ijtld.11.0060
|View full text |Cite
|
Sign up to set email alerts
|

Intervention to increase detection of childhood tuberculosis in Bangladesh

Abstract: Simple guidelines and training on child TB case detection, together with basic logistics support, can be integrated into the existing National TB Control Programme and improve service delivery to children in TB-endemic areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 3 publications
1
24
0
Order By: Relevance
“…15 This confirms that constitutional symptoms and signs play a key role in detecting TB in children, and, unfortunately, these can be missed when there is no follow-up assessment. 16 The only case with confirmed TB was a 4-year-old boy who expectorated sputum spontaneously. Only a small minority of children at this age have developed the oral-motor skills and the ability to cooperate with expectorating sputum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 This confirms that constitutional symptoms and signs play a key role in detecting TB in children, and, unfortunately, these can be missed when there is no follow-up assessment. 16 The only case with confirmed TB was a 4-year-old boy who expectorated sputum spontaneously. Only a small minority of children at this age have developed the oral-motor skills and the ability to cooperate with expectorating sputum.…”
Section: Discussionmentioning
confidence: 99%
“…However, around 15. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].3% of the population remains uninsured. 7 In addition, access to health care for the purposes of diagnosing TB differs according to the provider's regimen.…”
Section: Introductionmentioning
confidence: 99%
“…1 One reason may be poor case-detection in children due to diagnostic challenges, and the potential to increase case detection has been illustrated in a recent study from Bangladesh. 11 However, there is also likely to be considerable under-reporting. A recent study from Indonesia reported that less than 2% of children diagnosed and treated for tuberculosis in Java were reported to the NTP.…”
Section: Examples Of Recent National Initiatives For Implementationmentioning
confidence: 99%
“…For example, health care workers need to be better trained to recognise the symptoms and signs of TB, as better awareness of health workers at microscopy centres has led to an increase in the case detection of TB in children in Bangladesh. 20 Sputum smear microscopy has low sensitivity for diagnosing TB, and other diagnostic modalities should be considered. An important diagnostic development is a sensitive, specific, fully automated and commercially available nucleic acid amplification test, the Xpert ® MTB/RIF assay (Cepheid Inc, Sunnyvale, CA, USA) for use with sputum and other body specimens.…”
Section: Public Health Actionmentioning
confidence: 99%